Quantitative electrophoretic deposition of nanocrystal films from non-aqueous suspensions - Panta, Krishna Raj (Kansas State University, 2022)
This study presents a novel method to correlate the mass and charge transfer kinetics during the electrophoretic deposition of nanocrystal films by using a purpose-built double quartz crystal microbalance combined with simultaneous current-measurement. Our data support a multistep process for film formation: generation of charged nanocrystal flux, neutralization via charge transfer at the electrode, and polarization of neutral nanocrystals near the electrode surface. The neutralized particles are then subject to dielectrophoretic forces that reduce diffusion away from the interface, generating a sufficiently high neutral particle concentration at the interface to form a film. The correlation of mass and charge transfer enables quantification of the nanocrystal charge, the fraction of charged nanocrystals, and the initial sticking coefficient of the particles. These quantities permit calculation of the film thickness, providing a theoretical basis for using concentration and voltage as process parameters to grow films of targeted thicknesses.
Keywords: Double quartz crystal microbalance; Nickel nanocrystals; Electric-field assisted nanocrystal film; Dielectrophoresis; Diffusion; Migration